Dynamic thermomechanical response and constitutive modeling of eutectic high-entropy alloy. (15th May 2023) - Yuan, Kangbo; Yao, Xiaohu; Yu, Yongqi; Wang, Ruifeng; Chai, Zishu; Zhou, Kexuan; Wang, Zhijun
Highlights: LMD Ni32Al18 alloy has lower strength and higher ductility than the arc melted counterpart. Anisotropy in flow stress of LMD sample is found and it does not change with the strain rate. LMD and arc melted Ni32Al18 alloys exhibit different rate-temperature coupling effects. A viscoplastic constitutive model is developed for LMD and arc melted Ni32Al18 alloys. Ni32Al18 alloy exhibits superior dynamic specific yield strength at high temperature. Abstract: Since the eutectic high-entropy alloys (EHEAs) have been expected to be candidates for superalloys at the beginning of their invention, getting insights into their high-temperature mechanical performance under impact loadings is of particular significance for exploring their application potential in extreme service environments with high temperature and high strain rate. Meanwhile, additive manufacturing methods have been found to be very suitable for preparing EHEAs in the past two or three years. Therefore, this work, as the first attempt, carries out a comparative study on the microstructural and dynamic thermomechanical performances of the Ni32 Co30 Cr10 Fe10 Al18 (Ni32 Al18 ) EHEA manufactured by the laser metal deposition (LMD) and arc melting. The uniaxial compressive responses are tested over a strain rate range of 0.001/s∼7000/s and a temperature range of 77 K∼1123 K. The difference in microstructures and plastic flow behaviors between the LMD and the arc melted samples are revealed. The results show that the LMD samples feature a combination of the primary FCC phases and the typical lamellar eutectic structures, while the arc melted samples possess only ultrafine lamellar eutectic structures. The LMD samples exhibit lower strength and higher ductility than the arc melted ones. The high strength in the arc melted samples is attributed to the high athermal resistance of the dense lamellar structures (composed of ultrafine FCC and B2 phases) to mobile dislocations, while the primary FCC phases lead to high ductility and strain hardening ability in the LMD samples. The anisotropy in flow stress of the LMD sample is found at each strain rate and attributed to the different phase boundary densities generated by the LMD route in different directions. Then, a viscoplastic constitutive model considering the microstructural features is developed, which can reflect the size effect of grains and phases on flow stress, as well as the influence of the phase content on the rate-temperature coupling effect. This model is demonstrated to successfully predict the dynamic plastic flow behavior of both the LMD and arc melted Ni32 Al18 EHEA over a wide range of temperature. Furthermore, the Ni32 Al18 EHEA is found to have superior high-temperature dynamic specific yield strength compared to several existing typical superalloys. Graphical abstract: Image, graphical abstract